Prevalence and risk factors of long COVID-19 persisting for 2 years in Hainan Province: a population-based prospective study - Daya Zhang; Chen Chen; Yunqian Xie; Shuo Zhou; Da Li; Fan Zeng; Shimei Huang; Yanting Lv; Xianfeng Huang; Fengjiao Mao; Jinglei Kuang; Jin Gan; et al. (Scientific Reports)
Abstract Coronavirus disease 2019 (COVID-19) can lead to persistent symptoms, sequelae, and other medical complications that may last for weeks or months after recovery. The aim of the study is to assess the prevalence and risk factors of long COVID-19 persisting for 2 years in Hainan Province, China, to aid in its recognition, prevention, and treatment. Between July and August 2022, 960 individuals with confirmed SARS-CoV-2 infection in Hainan, China, were recruited. An epidemiological questionnaire was conducted via phone interviews to assess participants’ recovery status after 2 years. Among the participants, 120 patients (12.5%) experienced at least one long COVID-19 complication. The most common symptoms were cough (33.3%, 40/120), followed by fatigue (25.9%, 31/120), hair loss (23.3%, 28/120), and dizziness (20.8%, 25/120). Independent risk factors included age over 65, moderate to severe infection, chronic diseases, irregular diet, late sleeping, anxiety, and fewer than 2 vaccinations (p < 0.05). While most individuals infected with COVID-19 fully recover, approximately 12.5% experience intermediate or long-term effects. This study is the first to identify the incidence and associated risk factors of long COVID-19 with the longest follow-up time, providing valuable insights for the timely restoration of pre-COVID-19 health.